ENGLISH LANGUAGE EDUCATION STUDENTS PERCEPTIONS OF SELF EFFICACY IN PUBLIC SPEAKING CLASS - Wijaya, Kristian Florensio; Mbato, Concilianus Laos (Journal of English Language Teaching and Linguistics, 2020)
Self-efficacy is one of the most pivotal springboards determining EFL learners? success in acquiring the target language in the communicative classroom contexts. Therefore, well-planned learning strategies and enjoyable learning environments should be provided continuously in order to breed proficient communicators in the target language. To do so, English language teachers need to shift their roles from instructors as facilitators facilitators to nurture EFL learners? self-efficacy development continuously. This study aimed to investigate the students? perceived self-efficacy in public speaking class. One research problem was proposed in this study namely, what are the significant factors that can heighten learners? self-efficacy in public speaking class? This study employed a qualitative method utilizing three research instruments i.e., classroom survey, students? speaking learning reflections, and interview to collect data from public speaking class of the English Education Study Program, Sanata Dharma University, Yogyakarta. Qualitative content analysis was employed to draw meanings out of the data gathered. Findings from this study revealed that EFL learners will be able to be proficient target language communicators when they believe in their speaking competencies and obtain meaningful feedback from the teachers.